FASILITAS PENANGANAN HEWAN TERLANTAR - Cecilia Evelina; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2021)
The development of technology and society's economy is one of the driving factors for growth in an urban environment. This development does not only occur in physical terms, but there is also a shift in the social and cultural elements of society. The nature of urban society tends to be individualistic, capitalist, more concerned with speed or something that is considered instant and is no longer familiar with nature, plants, and animals. Things that are considered unprofitable tend to be removed. Humans, animals and plants should coexist even if an area has turned into a big city. The existence of abandoned animals is an inseparable component of life in urban areas. The population of animals such as stray dogs and stray cats that continue to soar will certainly affect the ecosystem in urban areas. In the end, the disruption of the ecosystem will also affect human life, such as increasing the spread of diseases from animals to humans to increasing road accidents. For this reason, human efforts are needed to deal with the problems of street animals which are actually an inseparable part of the city, as well as efforts to bring the interaction between city humans and animals closer. Rengkuh is also present as a project that seeks to become a container for handling abandoned animals on the streets of BSD City. Keywords: Ecology; Pet; Stray Animal; Urban; Rengkuh Asuh Abstrak Perkembangan teknologi dan ekonomi masyarakat menjadi salah satu faktor pendorong terjadinya pertumbuhan di suatu lingkungan urban. Perkembangan itu tidak hanya terjadi dalam segi fisik, melainkan juga terdapat pergeseran pada unsur sosial dan budaya dari masyarakat. Sifat masyarakat urban cenderung individualistis, kapitalis, lebih mementingkan kecepatan atau sesuatu yang dianggap instan, serta tidak lagi akrab dengan alam, tumbuhan dan hewan. Hal yang dianggap tidak menguntungkan cenderung disingkirkan. Manusia, hewan dan tumbuhan seharusnya hidup berdampingan meskipun suatu wilayah telah berubah menjadi sebuah kota besar. Keberadaan hewan terlantar merupakan komponen yang tidak dapat terpisahkan di dalam kehidupan di perkotaan. Populasi dari hewan seperti anjing dan kucing jalanan yang terus melonjak tentu akan mempengaruhi ekosistem di dalam perkotaan. Pada akhirnya terganggunya ekosistem itu juga akan turut mempengaruhi kehidupan manusia, seperti meningkatnya penyebaran penyakit dari hewan ke manusia hingga peningkatan kecelakaan di jalanan. Untuk itu diperlukan upaya manusia untuk menangani permasalahan dari hewan jalanan yang sebenarnya juga merupakan bagian yang tidak terpisahkan dari kota, juga upaya mendekatkan kembali interaksi antara manusia kota dengan hewan. Rengkuh Asuh pun hadir menjadi sebuah proyek yang berupaya menjadi wadah penanganan hewan terlantar di jalanan Kota BSD.